Antioxidant Activity of DPPH Method on Stone Banana Flour with Blanching Drying and Temperature Treatment - Ni Wayan Yulia Andriani; Ni Made Ayu Suardani Singapurwa; A.A. Made Semariyani (International Journal of Scientific Multidisciplinary Research, 2023)
Stone banana is a type of banana that has seeds in the fruit. Ares is a young banana stem. Banana stems called ares, located on the inside of banana stems. The objective of this research was to identify the antioxidant capabilities of stone banana fields as they are dried and heated with a UV-Vis spectrophotometer. The results showed that stone banana ares flour has very weak antioxidant activity. It's characterized by an IC50 value of over 500 ppm, which can be interpreted as having a low activity or potential as an antioxidant. The solar drying method and blanching temperature of 85 °C obtained the smallest IC50 average value of 42,429.90 ppm with a very weak category